The impact of vaping on tooth enamel and mucous membranes - Rudenka, Alona (Global Prosperity, 2025)
Abstract. This article is devoted to determining the impact of vaping on tooth enamel and mucous membranes. In recent years, vaping has become widespread as an alternative form of nicotine consumption. The question of its safety for human health still needs to be resolved. Given the direct contact of electronic cigarette aerosols with the tissues of the oral cavity, it is important to establish their impact on tooth enamel and mucous membranes. The study analyzed current scientific data on the effects of vaping on hard and soft tissues of the oral cavity and identified clinical manifestations, mechanisms, and diagnostic markers of damage. It was shown that scientists are studying changes in tooth enamel, mucous membrane, and oral microbiome in people who use electronic cigarettes. It has been established that regular vaping contributes to changes in the physicochemical properties of enamel, a decrease in its hardness, and an increase in the roughness of its surface, which creates conditions for dental plaque adhesion and an increased risk of caries. The oral mucosa undergoes chronic irritation, inflammatory changes, and a decrease in regenerative potential. This is associated with the cytotoxic effect of vape aerosol components, the activation of oxidative stress, and the disruption of the epithelial barrier. In addition, changes in the normal composition of the oral microbiome and a shift in its functional activity in a pro-inflammatory direction play a major role in the pathogenesis of enamel disorders. The data obtained indicate that vaping is dangerous for the condition of the enamel and oral mucosa. This should be taken into account by dentists when assessing the condition of the oral cavity and developing preventive measures.